Oxidation and hydrogenation of monolayer MoS2 with compositing agent under environmental exposure: The ReaxFF Mo/Ti/Au/O/S/H force field development and applications - Mao, Qian; Zhang, Yuwei; Kowalik, Malgorzata; Nayir, Nadire; Chandross, Michael; van Duin, Adri C. T. (Frontiers in Nanotechnology, 2022)
An atomistic modeling tool is essential to an in-depth understanding upon surface reactions of transition metal dichalcogenides (TMDs), such as molybdenum disulfide (MoS2), with the presence of compositing agents, including Ti and Au, under different environmental exposures. We report a new ReaxFF reactive force field parameter set for Mo, Ti, Au, O, S, and H interactions. We apply the force field in a series of molecular dynamics (MD) simulations to unravel the impact of the Ti dopant on the oxidation/hydrogenation behaviors of MoS2 surface. The simulation results reveal that, in the absence of Ti clusters, the MoS2 surface is ruptured and oxidized at elevated temperatures through a process of adsorption followed by dissociation of the O2 molecules on the MoS2 surface during the temperature ramp. When the MoS2 surface is exposed to H2O molecules, surface hydrogenation is most favored, followed by oxidation, then hydroxylation. The introduction of Ti clusters to the systems mitigates the oxidation/hydrogenation of MoS2 at a low or intermediate temperature by capturing the O2/H2O molecules and locking the O/H-related radicals inside the clusters. However, OH- and H3O+ are emitted from the Ti clusters in the H2O environment as temperature rises, and the accelerating hydrogenation of MoS2 is consequently observed at an ultra-high temperature. These findings indicate an important but complex role of Ti dopants in mitigating the oxidation and hydrogenation of MoS2 under different environmental exposures. The possible mechanisms of oxidation and hydrogenation revealed by MD simulations can give an insight to the design of oxidation resistant TMDs and can be useful to the optical, electronic, magnetic, catalytic, and energy harvesting industries.